Company Forms in Digital Economy Era - Arifiyanto, Joiverdia (Talenta Publisher, 2023)
The acceleration of globalization driven by the massive development of information and communication technology in all sectors of human life has changed human attitudes and lifestyles. This change then creates an awareness that creative and innovative human resources are more reliable than just industrial strength. This awareness encourage the birth of a creative economy that focuses on industries based on creativity and talent. Indonesia’s creative economy has entered the digital economy era. Basically, Indonesia is a potential country in the Creative Economy, but has problems with global marketing. The creative economy focuses on goods and services based on talent and expertise with an orientation towards overcoming unemployment problems and encouraging the development of companies based on the economic potential of a region. The element of the creative industry is a combination of intellectuals with art, technology or business that work in a synergy. One of the driving forces of Indonesia’s creative economy is MSMEs. Marketing problems through new business forms such as startups open up special opportunities for MSME business entities that can take advantage of e-commerce models that provide direct buying and selling services on online website or act as shopping center service providers